Contaminated faucets and sinks as a reservoir for antibiotic-resistant bacterial transmission in healthcare settings - Qiao Li; Honghui Ding; Zhongju Chen; Wenyuan Li; Kun Tan; Chuan Xu; Mingjun Zou; Xiao Wang; Li Tan (Journal of Infection in Developing Countries)
Introduction: Multidrug-resistant bacterial infection has emerged as a global hygiene threat in hospitals, and outbreaks cause increased patient morbidity and mortality in the healthcare system. Mounting evidence points to faucets and sinks as the culprits in the outbreaks of multidrug-resistant bacterial infections. However, the mechanism and the route through which faucets and sinks contribute to antibiotic-resistant bacterial transmission are not fully understood.